The fatigue behavior of irradiated Reactor Pressure Vessel steel. (December 2017) - Zhong, W.; Tong, Z.; Ning, G.; Zhang, C.; Lin, H.; Yang, W.
Abstract: Fatigue specimens of A508-3 steel were irradiated in the swimming-pool test reactor in China Institute of Atomic Energy, the fluence was 3 × 10 19  n/cm 2 at 300 °C, then low-cycle fatigue tests were carried out at ambient temperature, with the fatigue strain range is 0.32–1.8%. The results indicate that, irradiated A508-3 specimens exhibit cyclic softening and instability behavior during the test, and the cyclic softening rate increased with strain range increased; fatigue life decreased from 1.7 × 10 5 to about 5 × 10 2, as the strain range increased from 0.32% to 1.8%, the fatigue life of A508-3 steel increased after the neutron irradiation; fatigue fracture initiated at the surface of specimen, and more individual cracks formed on the specimens of higher strain range compared with the specimens of lower strain range. Highlights: The fatigue property of irradiated Reactor Pressure Vessel steel was test. The fatigue property of irradiated and unirradiated Reactor Pressure Vessel steel was compared. The RPV steel fatigue life increased after neutron irradiation.